Are symptoms of insomnia in primary care associated with subsequent onset of dementia? A matched retrospective case-control study. (1st September 2020) - Hoile, Richard; Tabet, Naji; Smith, Helen; Bremner, Stephen; Cassell, Jackie; Ford, Elizabeth
Abstract: Objective: There is evidence from neuroimaging studies of an association between insomnia and early dementia biomarkers, but observational studies have so far failed to show a clear association between insomnia and the later development of dementia. We investigated the association between dementia diagnosis and recording of insomnia symptoms 5–10 years earlier in primary care. Method: A case-control study using data from the Clinical Practice Research Datalink. 15, 209 cases with dementia (either Alzheimer's, vascular, mixed or non-specific subtypes) at least 65 years old at time of diagnosis, were matched with the same number of controls on year of birth and gender. We ascertained the presence of insomnia symptoms during a five-year period starting 10 years before the index date. Odds ratios for developing dementia were estimated using logistic regression after controlling for hypnotic exposure and physical and mental health comorbidities. Results: The adjusted odds ratio for dementia in those with previous insomnia was 1.34 (95% CI = 1.20–1.50). Conclusion: There is an association between dementia and previous insomnia. It may be possible to incorporate insomnia into predictive tools for dementia.